Política de memória no Brasil: Raça e história em Oliveira Vianna Gilberto Freyre - Jaime Ginzburg (Araucaria)
This essay tries to examine politics of memory in Brasil, according to ideas presented by Nelly Richard, Pieter Duvenage and Theodor Adorno. The purpose is to show how images of the past can bring trouble to the ways we develop contemporary debates. Considering information referring to 1920- 1945, we consider as a strong case the debate between Gilberto Freyre and Oliveira Vianna. It is wrong to develop reflections corcerning this period, without considering the differences between their positions, referring to racial issues.